Synthesis and Characterization of Some Novel Complexes of Iron(III) with Ketoanil Schiff Base - Pathak, Prince; Singh, Monal; Pathak, Vishal (Asian Journal of Chemistry, 2010)
The present communication is related to investigate structure of newly developed molecular models prepared by the interaction of a typical ketoanil Schiff's base, p-phenyldianil of 2- thiophene glyoxal (PDATG) with Fe(III) salts. Stoichiometries of the complexes have been established from the data of their analysis. For the identification of modes of coordination and to investigate structural change in ligand during interaction with metal ions, infrared data of ligand have been compared with those of complexes. Absorption spectra falling in the visible range have been studied in conjugation with ligand field theory. Different values of g, g|| and g⊥ have been calculated at room temperature and liquid nitrogen temperature from ESR spectrum of each sample.